HERPES ZOSTER DURING IMMUNOSUPPRESSIVE THERAPY FOR AUTOIMMUNE DISEASES - Zahid, Mohammad Faizan; Ghufran, Mariam; Mansoor, Armaghan-e-Rehman; Sohail, Muhammad Rizwan (Journal of Ayub Medical College Abbottabad, 2017)
Background: Patients on immunosuppressive therapy are at a greater risk for herpes zoster reactivation and are more likely to have adverse outcomes. Propylactic antivrials and vaccinations may potentially prevent these complications. Methods: Medical literature addressing the clinical course and therapy of herpes zoster in patients receiving immunosuppressive therapy for autoimmune disorders, and the roles of anti-viral prophylaxis and vaccination was reviewed. Research databases including PubMed, Ovid, Medline, Google Scholar and Cochrane were utilized. Results: Acyclovir and its derivatives are most commonly used in this setting for treatment and reduction of post-zoster complications. Foscarnet may be used for acyclovir-resistant strains. At both conventional and ultra-low doses, acyclovir has proven effective when used as prophylaxis, reducing the incidence of zoster and its complications in immunosuppressed patients. Additionally, ultra-low doses are associated with significantly reduced side effects. The zoster vaccine, Zostavax, a live-attenuated vaccine has shown promising results in several clinical trials. However, live-attenuated vaccines should be cautiously used in immunosuppressed patients. For patients who require immunosuppressive therapy, vaccination 2-3 months prior to therapy may be appropriate. Conclusions: Prophylactic antiviral therapy and vaccination help significantly reduce morbidity and mortality from zoster reactivation in patients receiving immunosuppressive therapy. Keywords: Herpes zoster; Autoimmune diseases; Immunosuppressive therapy; Prophylaxis; Vaccination